Perancangan Permainan Digital â€œKronik Majapahitâ€ Sebagai Media Pembelajaran Sejarah Sumpah Palapa Untuk Remaja - Rahman, Yanuar; Hertiasa, Hendy (Jurnal Bahasa Rupa, 2018)
History is a reflection to characters of the nation that should not be forgotten, because there are so many lessons and could be gained by understanding it. But in reality history lessons did not always get a proper place in the learning process of students in high school. This research wants to dig deeper and find alternative solutions for historical learning process, especially about how to introduce chronological history of the sumpah palapa through an exciting gaming media as part of the learning process to teenagers. The research process is also looking for alternative ways of designing gameplay and visually appropriate for the game. The method used in this research is a systematic and continuous action reserach, to understand the context of learning used constructivism learning methods, as well as related theories in the realm of education and psychology in order to enrich the rationale of this research. The results of the research produced through literature review, observation, discussion and experiments to obtain data, will be used as a basis in the design of content and visual games. A final challenge of this game design process is to create a game that contextual and parallel with the goal of teaching history in Indonesia, as a means to develop the good character of young people for the nation by strengthen the sense of history to the youth as the primary user.